Weather - Simon, Seymour ([Washington, D.C.] : Smithsonian ; New York : Collins, 2006)
Explores the causes, changing patterns, and forecasting of weather.
Keywords: Weather -- Juvenile literature; Meteorology -- Juvenile literature; Weather; Meteorology